1995
DOI: 10.1093/brain/118.1.153
|View full text |Cite
|
Sign up to set email alerts
|

Covert visuospatial attentional mechanisms in Parkinson's disease

Abstract: Orienting and focusing of attention were assessed in 32 Parkinson's disease and 32 control subjects. No differences were found in the covert orienting of attention, suggesting that the Parkinson's disease subjects of the current study were not impaired in the ability to orient attention towards an expected source of stimulation. However, with the process of modulating the attentional focus or of managing more than one attentional task, dysfunction in Parkinson's disease subjects became apparent. The observed r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 0 publications
2
19
0
1
Order By: Relevance
“…The reduced costs in patients at the longest SOA supports the idea that disengagement of attention from the cued location was faster in patients than in controls. Although, the results of the present study seem to be consistent with several studies investigating voluntary visual spatial shifts of attention two studies did not obtain the same ®ndings (Bennett et al, 1995;Hsieh et al, 1996). Bennett et al only found impaired performance in PD patients when both cueing (orienting) and focussing (by increasing the box contour sizes) was manipulated, thereby increasing attentional resource demands of the task.…”
Section: Discussionsupporting
confidence: 67%
“…The reduced costs in patients at the longest SOA supports the idea that disengagement of attention from the cued location was faster in patients than in controls. Although, the results of the present study seem to be consistent with several studies investigating voluntary visual spatial shifts of attention two studies did not obtain the same ®ndings (Bennett et al, 1995;Hsieh et al, 1996). Bennett et al only found impaired performance in PD patients when both cueing (orienting) and focussing (by increasing the box contour sizes) was manipulated, thereby increasing attentional resource demands of the task.…”
Section: Discussionsupporting
confidence: 67%
“…Although nondemented PD patients often perform similarly to neurologically healthy individuals on tests that require the facilitatory aspects of orienting (Bennett, Waterman, Scarpa, & Castiello, 1995; Goldman, Baty, Buckles, Sahrmann, & Morris, 1998), they frequently are impaired when conditions promote a conflict between task-relevant and irrelevant information, such as on tests of selective attention (Filoteo, Maddox, Ing, & Song, 2007), negative priming (Mari-Beffa, Hayes, Machado, & Hindle, 2005), set shifting (Downes et al, 1989), and inhibition of return. Inhibitory attention and working memory involve overlapping processes, and space-based and object-based aspects of these processes are functionally and neurally separable (Chou & Yeh, 2008; Simmonds, Pekar, & Mostofsky, 2008; Zhou & Chen, 2008).…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…In particular, it has been suggested that these patients have an attention deficit that is mediated by impaired inhibitory processes (Filoteo, Rilling, & Strayer, 2002). Although nondemented PD patients often perform similarly to neurologically healthy individuals on tests that require the facilitatory aspects of orienting (Bennett, Waterman, Scarpa, & Castiello, 1995; Goldman, Baty, Buckles, Sahrmann, & Morris, 1998), they frequently are impaired when conditions promote a conflict between task-relevant and irrelevant information, such as on tests of selective attention (Filoteo, Maddox, Ing, & Song, 2007), negative priming (Mari-Beffa, Hayes, Machado, & Hindle, 2005), and set shifting (Downes et al, 1989). It should be noted, however, that PD patients can perform normally on some attention tasks that require inhibition (Grande et al, 2006; Possin, Cagigas, Strayer, & Filoteo, 2006).…”
mentioning
confidence: 99%